Molecular detection of Anaplasma platys infection in free-roaming dogs and ticks from Kenya and Ivory Coast. Issue 1 (December 2016) - Matei, Ioana; D'Amico, Gianluca; Yao, Patrick; Ionică, Angela; Kanyari, Paul; Daskalaki, Aikaterini; Dumitrache, Mirabela; Sándor, Attila; Gherman, Călin; Qablan, Moneeb; Modrý, David; Mihalca, Andrei
Abstract Background Anaplasma platys is a bacterium parasitic in the canine platelets, representing the causative agent of canine cyclic thrombocytopenia, with a worldwide distribution, mainly in tropical countries. The agent has zoonotic potential, being reported in several human clinical cases. The suspected vector is the tickRhipicephalus sanguineus (sensu lato ), widely distributed in animals and humans in the tropical regions of South America, Africa, Asia and Australia, but also in southern Europe. Only few scattered data concerning the epidemiology ofA. platys in sub-Saharan Africa are available. The aim of our study was to evaluate the epidemiological status ofA. platys in dogs and cats from rural communities in eastern and western Africa, where dogs and their ticks live in close contact with humans. Methods A total of 216 canine and 22 feline blood samples and ticks feeding on them were collected in 2013 and 2014 from eight localities in Ivory Coast and four localities in Kenya. PCR was performed using specific primers targeting a portion of the 16S rRNA gene, followed by sequencing. Results The main results highlight the high prevalence ofA. platys infection in dogs in both Eastern and Western Africa and report it for the first time in Eastern Africa and inRhipicephalus camicasi . Conclusions The presence ofA. platys DNA inR. camicasi feeding on negative hosts together with the relatively high prevalence ofA. platys, correlated with the absence of the probable vectorRhipicephalus sanguineus (s.l .) in Kenyan Island suggest the involvement of other tick species in the transmission ofA. platys .